Spolno kazensko pravo: od starega veka do današnjega kazenskopravnega obvladovanja spolnosti - Stajnko, Jan (Pravnik, 2025)
Monograph Sexual Criminal Law: From Antiquity to Present-Day Efforts to Manage Sexuality by Means of Criminal Law presents the turbulent topic of sexual offences in a scientific, concise, and systematic manner. The core of the monograph consists of a historical legal study, a comparative analysis of a long list of sexual offences and a review of a relevant international and EU legislation. The authors, Damjan Korošec, Sabina Zgaga Markelj, and Vid Žepič, have produced a work that will remain an integral part of any serious examination of sexual criminal law for years to come. Simultaneously, the monography is valuable for case law. In this respect, suggested interpretations and warnings against pitfalls lurking in the divisive 2021 amendment to the Slovenian Criminal Code KZ-1H are especially topical.
Keywords: children; criminal law; history; ja pomeni ja; kazensko pravo; nasilje; otroci; posilstvo; rape; recenzije; sexuality; spolnost; violence; yes means yes; zgodovina